Sharāʼit-i asāsī faʻālīyat́hāyi ṣanāʻatī - Fidāʼī, Fidā Muḥammad (Nashriyāti Mujallahʼī Iqtiṣād, Riyāsat-i ʻUmūmī Utāq́hāyi Tijārat, 1961)
On the development of industries; historical study, with reference to Afghanistan.